A proposal on ultra-low cycle fatigue damage evaluation of structural steels. (August 2021) - Li, Shuailing; Xie, Xu; Tian, Qin; Zhang, Zhicheng; Cheng, Cheng
Highlights: A one-parameter ultra-low cycle fatigue damage model of structural steels proposed. The parameter of proposed model calibrated using tensile tests of coupon specimens. The proposed model gives reasonable accuracy on ultra-low cycle fatigue evaluation. Abstract: The ductile crack initiation observed in structural steels subjected to ultra-low cycle fatigue (ULCF) loading often leads to the catastrophic failure in steel structures. In the existing ULCF damage models, there is always a contradiction between the cost of model parameters calibration and prediction accuracy. In order to solve the contradiction, a one-parameter model for ULCF damage evaluation of structural steels was proposed based on the concept that ULCF damage consists of ductile damage in tensile loading and cyclic damage under cyclic plastic stain loading, and a simple and practical parameter calibration method only using tensile results of coupon specimens is developed. Tests and finite element analysis were carried out on circular notched specimens to verify the prediction accuracy of proposed model. The results show that predicted results are in good agreement with test results, indicating a good performance of the proposed model for ULCF damage evaluation of structural steels.